2003
DOI: 10.1093/brain/awg242
|View full text |Cite
|
Sign up to set email alerts
|

Dosage‐sensitive X‐linked locus influences the development of amygdala and orbitofrontal cortex, and fear recognition in humans

Abstract: The amygdala, which plays a critical role in emotional learning and social cognition, is structurally and functionally sexually dimorphic in humans. We used magnetic neuroimaging and molecular genetic analyses with healthy subjects and patients possessing X-chromosome anomalies to find dosage-sensitive genes that might influence amygdala development. If such X-linked genes lacked a homologue on the Y-chromosome they would be expressed in one copy in normal 46,XY males and two copies in normal 46,XX females. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
156
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(173 citation statements)
references
References 84 publications
(98 reference statements)
16
156
1
Order By: Relevance
“…Collectively, aberrant (augmented) gray matter in orbital and medial prefrontal cortices, amygdale, and insula is in accord with the WSassociated neurobehavioral phenotype that includes hyperarousal, anxiety, altered or enhanced social impulses, enhanced emotional reactivity, and relatively strong face recognition skills. Interestingly, enlargement of the amygdala and orbitofrontal cortex also was reported recently in Turner syndrome (Good et al, 2003), a neurogenetic disorder associated with impaired social cognition and significant visual-spatial deficits.…”
Section: Discussionsupporting
confidence: 62%
“…Collectively, aberrant (augmented) gray matter in orbital and medial prefrontal cortices, amygdale, and insula is in accord with the WSassociated neurobehavioral phenotype that includes hyperarousal, anxiety, altered or enhanced social impulses, enhanced emotional reactivity, and relatively strong face recognition skills. Interestingly, enlargement of the amygdala and orbitofrontal cortex also was reported recently in Turner syndrome (Good et al, 2003), a neurogenetic disorder associated with impaired social cognition and significant visual-spatial deficits.…”
Section: Discussionsupporting
confidence: 62%
“…However, the presence and impact of co-existing psychiatric morbidity has received little attention. Indeed, neuro-imaging studies in women with TS have identified abnormalities in several brain regions relative to controls including the dorsolateral prefrontal cortex, amygdala, and hippocampus 4,7,[30][31][32][33] . The function of these brain regions also has been reported to be altered in mood disorders 34,35 , and, therefore, the neuroimaging data would suggest that women with TS may have an increased risk for the development of affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical features such as lymphedema, skeletal abnormalities and congenital heart and kidney defects are found in about 50% of affected individuals 1,2 . Brain development also may be affected in TS, with several neuroimaging studies reporting anatomical and functional differences between girls or women with TS and age-matched controls in the parietal and dorsolateral prefrontal cortices, superior temporal gyrus, hippocampal formation, amygdala, and temporal lobes [4][5][6][7][8] . Supporting the possibility of brain involvement, girls and women with TS Correspondence: Peter J. Schmidt, Behavioral Endocrinology Branch, Bldg.…”
Section: Introductionmentioning
confidence: 99%
“…Complementing the findings of atypical cerebral functioning seen in fMRI studies, neuroanatomic studies of TS have consistently found decreased gray matter volume in the bilateral parietal lobes, parieto-occipital region, and subcortical gray matter (Murphy et al, 1993;Reiss et al, 1995;Brown et al, 2002;Good et al, 2003;Kesler et al, 2003;Molko et al, 2003), as well as increased volume of the superior temporal gyrus (STG) (Kesler et al, 2003), amygdala (Kesler et al, 2004a,b), and orbitofrontal cortex (Good et al, 2003). Recent volumetric MRI localized parietal lobe findings to the bilateral superior parietal lobule and postcentral gyrus (Brown et al, 2004).…”
Section: Introductionmentioning
confidence: 88%